CTX-M-TYPE EXTENDED SPECTRUM ?-LACTAMASE-PRODUCING ESCHERICHIA COLI RESPONSIBLE FOR COMMUNITY URINARY INFECTIONS IN DOUALA-CAMEROON - Fewou, Simon Ngamli; Medjou Foffou, Fadel Laure; Manfouo Tuono, Romaric De (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Background: Informations regarding the resistance mechanisms of extended spectrum ß-lactamase (ESBL)-producing Escherichia coli during urinary tract infection in the community are keys to designing efficient therapeutic strategies in Douala, Cameroon. Therefore, we aimed at determining the prevalence and risks factors of CTX-M-type ESBL)-producing E coli infection among patients consulting at Douala Laquintinie hospital. Method: The samples were seeded on EMB medium and added to Cefotaxime. The Enterobacteriaceae strains were identified using an Api20 E gallery followed by an antibiogram carried out for the strains which were identified as Escherichia coli CTX-M to determine those producing ESBL and see their resistance profile to other families of antibiotics. The clinical and biological characteristics of the different participants were studied and analyzed using a statview statistical software. Results: We selected a total of 111 patients and identified 20 strains of Enterobacteriaceae. At the end of the biological analysis, of these 20 strains isolated, Escherichia coli was the most represented species (70%) followed by Klebsiella pneumoniae (20%). 14 strains of Enterobacteriaceae of the genus Escherichia coli of CTX-M type were obtained, among which 2 (14%) producers of Beta Lactamases with Broader Spectrum. These results showed Co resistance to other families of antibiotics including aminoglycosides (20 %) and fluoroquinolones (35 %). Conclusion. The results of this preliminary study show that the multi-resistant strains of Escherichia coli present in our region could be linked not only to self-medication (including traditional decoctions), and overuse of antibiotics but also to non-compliance hygiene rules by women.